2010
DOI: 10.1258/ebm.2010.010175
|View full text |Cite
|
Sign up to set email alerts
|

Preservation of the cardiac function in infarcted rat hearts by the transplantation of adipose-derived stem cells with injectable fibrin scaffolds

Abstract: Cell-based therapy can improve cardiac function but is limited by the low cell retention and survival within ischemic tissues. Injectable cardiac tissue engineering aims to support cell-based therapies and enhance their efficacy for cardiac diseases. So far, no research has been devoted to studying the usefulness of the combination of fibrin glue (as scaffold) and adipose-derived stem cells (ADSCs) to treat myocardial infarction. In our study, the rat ADSCs were isolated from subcutaneous adipose tissues. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(41 citation statements)
references
References 38 publications
0
41
0
Order By: Relevance
“…Conditioned media from hypoxia-treated ASCs can also improve cardiac function following infarction, possibly through their specific paracrine section of VEGF-A, bFGF, and TGF 1 [245]. Increased capillary densities/angiogenesis have also been reported using mouse ASCs injected into murine infarcts, with the ASCs taking up residence in the infarct area and EKGs showing stability of LVEF [246]; murine ASCs [247] or rat ASCs transplanted into rat infarcts resulting in significant improvement in heart function and tissue viability [248]; and human ASCs into rat infarcts, where not only increased peri-infarct capillary density is noted but increased numbers of nerve sprouts [249]. Finally, endothelial cells created from induced pluripotent ASCs (iPSCs) and injected into murine infarcts are found localized specifically around, but not directly integrated into, newly formed microvessels near the regenerating infarct region, suggesting paracrine action of these cells on the host vasculature [250].…”
Section: In Vivo Muscle Regenerationmentioning
confidence: 99%
“…Conditioned media from hypoxia-treated ASCs can also improve cardiac function following infarction, possibly through their specific paracrine section of VEGF-A, bFGF, and TGF 1 [245]. Increased capillary densities/angiogenesis have also been reported using mouse ASCs injected into murine infarcts, with the ASCs taking up residence in the infarct area and EKGs showing stability of LVEF [246]; murine ASCs [247] or rat ASCs transplanted into rat infarcts resulting in significant improvement in heart function and tissue viability [248]; and human ASCs into rat infarcts, where not only increased peri-infarct capillary density is noted but increased numbers of nerve sprouts [249]. Finally, endothelial cells created from induced pluripotent ASCs (iPSCs) and injected into murine infarcts are found localized specifically around, but not directly integrated into, newly formed microvessels near the regenerating infarct region, suggesting paracrine action of these cells on the host vasculature [250].…”
Section: In Vivo Muscle Regenerationmentioning
confidence: 99%
“…Despite many animal and clinical studies, previous studies 19,21,22 have focused on the effect of fibrin glue on 1 proliferation and differentiation potential of MSCs, and consequential replacement of damaged tissue. However, the contribution of fibrin glue to the paracrine effects of MSCs has not been examined.…”
Section: Introductionmentioning
confidence: 99%
“…17,20 Previous studies have also demonstrated that fibrin glue could improve the survival of injectable skeletal myoblasts, bone marrow cells, marrowderived cardiac stem cells, adipose-derived stem cells, and human induced pluripotent stem cell-derived cardiomyocytesin MI hearts. [21][22][23][24][25][26] Furthermore, injection of fibrin alone (without cells) could preserve cardiac function after MI and prevent negative LV remodeling. 27 Also, our previous report has demonstrated the positive role of platelet fibrin gel in cardiac repair after MI.…”
Section: Discussionmentioning
confidence: 99%